1990
DOI: 10.1259/0007-1285-63-749-337
|View full text |Cite
|
Sign up to set email alerts
|

The role of dacryocystography in the management of patients with epiphora

Abstract: A retrospective study has been carried out on 114 patients who have undergone dacryocystography (DCG) for epiphora, to assess the role of DCG in their management. It was found that 16/66 (24%) patients who were offered surgery after DCG refused it or were assessed as unfit for surgery, demonstrating the need for careful counselling and assessment of patients prior to investigation. The presence of lacrimal system obstruction on DCG was an important factor in determining whether a patient underwent lacrimal sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 8 publications
2
19
0
1
Order By: Relevance
“…Like syringing, this confirms the non-physiological character of dacryocystography [14]. In line with these observations, Nixon and colleagues concluded that the results of dacryocystography had no relevant influence on the choice of treatment [12].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Like syringing, this confirms the non-physiological character of dacryocystography [14]. In line with these observations, Nixon and colleagues concluded that the results of dacryocystography had no relevant influence on the choice of treatment [12].…”
Section: Discussionsupporting
confidence: 53%
“…Yet also this test is not physiological, since the lacrimal system is instrumented, and cannot be expected to give satisfactory functional information. The impact on treatment choice appears to be minimal [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has some Original advantages including safe and simple procedure, high sensitivity, high patient tolerance, low radiation dose to eye lens, however, the spatial resolution of this nuclear method is low and precise anatomical evaluation is not possible. This modality has been performed by instilling radiotracer in the inferior fornix of each eye and imaging of the ocular region with a gamma camera since 1972 and can detect the site of obstruction which help ophthalmologists to choose the best form of therapy [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…In the evaluation of LDS patency, dacryoscintigraphy or dacryoscintillography (DSG), a readily available, safe, objective, non-invasive, low-radiation-dose nuclear medicine method first introduced by Rossomondo and colleagues [7], and modified by numerous authors [8, 9], is expansively practiced. Even though it is useable not just in assessing LDS patency during diagnostic workup, but also in evaluating tear outflow following a lacrimal surgery, it allows solely planar, two-dimensional images, consequently its sensitivity and specificity need to be improved.…”
Section: Introductionmentioning
confidence: 99%